(3GdbGfhf aj GdWHs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg cdGe cdi ai GdSehe GdeTQhHI GUfGag GdSehe UfaGf s
(3BNQgG (B:s
(3KdGK ChGb KeGfjI YTQ CQHYI hYTQhf bjQGWkG Je GdcJGH GdNGeS ef cJGH GdbGfhf hgh ddGbQGHGPjf hJe HJeGeg cJGH GdbGfhf ai GdWH s
(3GdcJGH GdNGeS ai JQcjH GdGOhjI GdCbQGHGPjfs
(3Ydjg bQGAGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1311s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs